DPD Persoalan Dilematis Lembaga Perwakilan Daerah dalam Sistem Ketatanegaraan Indonesia - Rotua Tinambunan, Hezron Sabar; Oktafian Abrianto, Bagus (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 1 (2021)DO - 10.24843/JMHU.2021.v10.i01.p06, 2021)
The purpose of this research is to study and analyze the Dilemma Problems of Regional Representative Institutions in the Indonesian State Administration System, in this case the DPD which is a State institution in the category of state institutions using normative juridical categories through licensing in accordance with the demand (statute approach) and conceptual (approach conceptual), thus the DPD obligation related to the implementation of regional autonomy which is limited to providing an assessment also shows the weakness of the DPD's function because it cannot fight for regional interests in increasing the DPD's consideration which is not followed up by the DPR Tujuan dari penelitian ini adalah untuk meninjau dan menganalisis Persoalan Dilematis Lembaga Perwakilan Daerah Dalam Sistem Ketatanegaraan Indonesia dalam hal ini DPD yang merupakan lembaga Negara yang masuk kategori main state organ dengan menggunakan metode yuridis normatif melalui pendekatan perundang-undangan ( statute approach) dan pendekatan konseptual ( conseptual approch), bahwa Kewenangan DPD berkaitan dengan penyelenggaraan otonomi daerah yang sebatas memberikan pertimbangan pun menampakkan kelemahan fungsi DPD karena tidak dapat memperjuangkan kepentingan daerah terhadap kemungkinan pertimbangan DPD yang tidak ditindaklanjuti oleh DPR